Programming Primes (1968-1976): A Paradigmatic Program and Its Incarnations in the Age of Structured Programming - Bullynck, Maarten (History and philosophy of logic, 2015)
In response to the so-called 'software crisis' of the late 1960s, many approaches were proposed to turn (parts of) software engineering and programming into more systematic disciplines, to turn an art into a science. This paper studies one popular example often used in these proposals, the computation of a list of primes, to discuss some salient features of the proposed programming paradigms. It also looks at the actual implementation in the early 1970s of the prime program on a time-sharing system (MULTICS) and on a complex scientific computer (ILLIAC IV). Confronting theory with practice uncovers what the programming paradigms fail to grasp: the interaction with the user and the interaction with the machine.